2016
DOI: 10.1614/ws-d-14-00171.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Sulfentrazone Applied to Sugarcane Crop Residues

Abstract: The sulfentrazone is regularly applied to sugarcane crop harvest residue for PRE control of weedy species, especially in the dry season during the year, but little is known about how rainfall timing or crop residue mass affect the release of sulfentrazone into the soil and its subsequent effectiveness. Two experiments were conducted to examine the effects of sugarcane residue mass (5, 10, 15, and 20 t ha−1) and rainfall timing (1, 30, and 60 d after herbicide application) on sulfentrazone retention. Rainfall v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 20 publications
2
32
1
8
Order By: Relevance
“…Between 15% and 25% of the imazapic and tebuthiuron could not be desorbed from the litter with methanol extraction (Kessler et al 2015). In our study, there was a 30% to 40% decrease in herbicide recovery when rainfall was delayed for 1 d after application, although there was no additional decrease in recovery from 1 to 7 d. Other studies have demonstrated that herbicide recovery continues to decrease as time without rainfall increases from 1 to 60 DAT (Carbonari et al 2016;Cavenaghi et al 2007;Tofoli et al 2009).…”
Section: Speciescontrasting
confidence: 38%
“…Between 15% and 25% of the imazapic and tebuthiuron could not be desorbed from the litter with methanol extraction (Kessler et al 2015). In our study, there was a 30% to 40% decrease in herbicide recovery when rainfall was delayed for 1 d after application, although there was no additional decrease in recovery from 1 to 7 d. Other studies have demonstrated that herbicide recovery continues to decrease as time without rainfall increases from 1 to 60 DAT (Carbonari et al 2016;Cavenaghi et al 2007;Tofoli et al 2009).…”
Section: Speciescontrasting
confidence: 38%
“…Divine nightshade seed within their fluid‐filled fruit were more resilient than itchgrass when exposed to 150 and 200°C for 20 to 40 s. Burning post‐harvest sugarcane residue is a common practice in Louisiana in part because post‐harvest residue retention has shown to negatively affect ratoon yield in the subsequent season (Viator et al, 2009). In addition to crop yield loss from post‐harvest residue retention, residue can intercept soil‐applied pre‐emergence herbicides and allow weeds to germinate and compete with sugarcane (Carbonari et al, 2016). A report by Ball‐Coelho et al (1993) showed burned post‐harvest sugarcane residue could result in a maximum flame temperature of 121 to 288°C.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfentrazone persistence in the soil is long and proportional to the applied dose (Blanco et al, 2010). However, sulfentrazone is more available in sandy soils than in clayey textured soils due to the binding of herbicide molecules to the negative charges of soil colloids (Carbonari et al, 2016). Sulfentrazone persistence at a dose of 600 g ha -1 was estimated to be 376 days in a clayey Oxisol (Blanco and Velini, 2005).…”
Section: Introductionmentioning
confidence: 99%